Performing the Victorian : John Ruskin and Identity in Theater, Science, and Education - Weltman, Sharon Aronofsky, 1957- (Book collections on Project MUSE., 2007)
"This is the first book to examine John Ruskin's writing on theater. In works as celebrated as Modern Painters and obscure as Love's Meinie, Ruskin uses his voracious attendance at the theater to illustrate points about social justice, aesthetic practice, and epistemology. Opera, Shakespeare, pantomime, French comedies, juggling acts, and dance prompt his fascination with performed identities that cross boundaries of gender, race, nation, and species. These theatrical examples also reveal the primacy of performance to his understanding of science and education."--Jacket